User-friendly workflows for catchment modelling: Towards reproducible SWAT+ model studies. (December 2020) - Chawanda, Celray James; George, Chris; Thiery, Wim; Griensven, Ann van; Tech, Jaclyn; Arnold, Jeffrey; Srinivasan, Raghavan
Abstract: A Graphical User Interface (GUI) is regularly used to support model applications in catchment hydrological modelling software. A GUI is generally user-friendly for novice users but opens sources of irreproducible research. We illustrate that none of the 10 Soil and Water Assessment Tool (SWAT) models over the Upper Blue Nile can easily be reproduced. Scripted workflows provide the ability to reproduce model set-ups, but they may be less user-friendly especially to novice users. We present a software (SWAT + AW) that promotes reproducible SWAT + model studies while remaining user-friendly for both novice and expert users. SWAT + AW uses a configuration file to create models that are compatible with GUI. We applied the workflow to the Blue Nile catchment and show that it yields the same results the SWAT + GUI. We conclude that such user-friendly scripted workflows enhance reproducibility, transparency and reusability of hydrological models. The software is publicly available at https://github.com/VUB-HYDR/SWATPlus-AW . Highlights: Reviewed SWAT applications in the Blue Nile were not reproducible. We propose a user-friendly workflow that creates models from a configuration file while being interoperable with the GUI used to set up SWAT + models. It will be easy to reproduce models once data and the configuration file are publicly made available.